Mitochondrial genomes of three Mylabris (Pseudabris) species (Coleoptera: Meloidae, Mylabrini) and their phylogenetic implications - Cheng, Hai-Yun; Gao, Qi; Pan, Zhao (Zootaxa, 2023)
The complete mitogenomes of the subgenus Mylabris (Pseudabris) Fairmaire, 1894, endemic to the Qinghai-Xizang Plateau, are reported for the first time. Three species out of seven, M. hingstoni Blair, 1927, M. longiventris Blair, 1927, and M. przewalskyi (Dokhtouroff, 1887), were sequenced. The sequencing results of mitogenomes were annotated and analyzed. The gene arrangements were consistent with the putative ancestral insect mitogenomes as understood today, including 13 protein-coding genes (PCGs), 22 tRNAs, 2 rRNAs, and a noncoding internal control region (CR). The PCGs used the typical start ATN codon and TAA/TAG stop codons. The lengths of three mitogenomes were 15,692 bp, 15,685 bp, and 15,685 bp, with an A + T content of 71.29%, 71.67%, and 71.53%, respectively. The evolution rates of 13 PCGs were compared: The evolution rate of ATP8 was the highest, and that of COX1 was the lowest. Furthermore, the phylogenetic relationships among the genera and tribes of Meloidae were discussed.